Patient perspectives on stress after ICU and a short primary care based psychological intervention – results from a qualitative sub‑study of the PICTURE trial - Antina Beutel; Linda Sanftenberg; Chris M. Friemel; Robert Philipp Kosilek; Maggie Schauer; Thomas Elbert; Ulf-Dietrich Reips; Tomke Schubert; Sabine Gehrke-Beck; Konrad Schmidt; Jochen Gensichen; for the PICTURE study group (BMC Primary Care)
Abstract Background Approximately 20–25% of patients who survive medical treatment at an intensive care unit (ICU) develop post-traumatic stress symptoms. There is currently a gap in follow-up care for them. As part of the PICTURE study, general practitioners (GPs) carried out a brief interview-based intervention. The aim of this sub-study is to record the most distressing memories of ICU treatment from the patient’s perspective and their evaluation of a GP-based brief psychological intervention. Methods Participants were recruited from the intervention group of the main PICTURE study using selective sampling. All of them had experienced an ICU stay with mechanical ventilation and severe organ failure in the previous two years. They were interviewed about their experience of psychological stress during their ICU stay and their retrospective evaluation of the intervention. Semi-structured, guideline-based telephone interviews were conducted for this purpose, processed, and analyzed using the structuring qualitative content analysis based on Mayring. Findings When asked N = 8 patients about the most stressful memory of their stay at ICU, the main themes were helplessness, pain, fixation, inability to communicate and sleep disturbances. The question of amnesia regarding the stay in the ICU was answered affirmatively by half of the interviewees but was not experienced as stressful. The brief trauma-focused intervention carried out by their GPs was well received by all respondents. Conclusions The interviewees confirm that aversive traumatizing experiences are often associated with intensive care treatment and reinforce each other. These are due to the treatment setting but should be reduced wherever possible. In view of chronification and the lack of specific follow-up treatment options for these patients and the long waiting times for psychotherapy, the implementation of low-threshold treatment options by GPs appears to be ideally suited to closing this gap in care, particularly for patients with mild to moderate symptoms of a post-traumatic stress disorder. Trial registration The main trial was registered at ClinTrials gov (NCT03315390) and at the German Register of Clinical Trials (DRKS, DRKS00012589) on 17/10/2017.